GDF15 is required for maintaining subcutaneous adipose tissue lipid metabolic signature - Carla Igual-Gil; Christopher A. Bishop; Markus Jähnert; Kornelia Johann; Verena Coleman; Vanessa Baum; Michael Kruse; Andreas F.H. Pfeiffer; Olga Pivovarova-Ramich; Mario Ost; Maximilian Kleinert; Susanne Klaus (Scientific Reports, 2024)
Abstract Recent research has identified growth differentiation factor 15 (GDF15) as a crucial factor in various physiological and pathological processes, particularly in energy balance regulation. While the role of GDF15 in modulating energy metabolism through hindbrain GDNF family receptor alpha-like (GFRAL) signaling has been extensively studied, emerging evidence suggests direct peripheral metabolic actions of GDF15. Using knockout mouse models, we investigated GDF15 and GFRAL’s roles in adipose tissue metabolism. Our findings indicate that C57BL/6/129/SvJ Gdf15-KO mice exhibit impaired expression of de novo lipogenesis enzymes in subcutaneous adipose tissue (sWAT). In contrast, C57BL/6J Gfral-KO mice showed no impairments compared to wild-type (WT) littermates. RNA-Seq analysis of sWAT in Gdf15-KO mice revealed a broad downregulation of genes involved in lipid metabolism. Importantly, our study uncovered sex-specific effects, with females being more affected by GDF15 loss than males. Additionally, we observed a fasting-induced upregulation of GDF15 gene expression in sWAT of both mice and humans, reinforcing this factor’s role in adipose tissue lipid metabolism. In conclusion, our research highlights an essential role for GDF15 in sWAT lipid metabolic homeostasis. These insights enhance our understanding of GDF15’s functions in adipose tissue physiology and underscore its potential as a therapeutic target for metabolic disorders.